A cupin domain is involved in α-amylase inhibitory activity. (December 2018) - Wang, Zhankui; Chen, Ming; Zhang, Yaqin; Huang, Liyan; Wang, Shuang; Tao, Yuan; Qian, Peipei; Mijiti, Abudoukeyumu; Gu, Aixing; Zhang, Hua; Shi, Shubing; Cheng, Hui; et al.
Highlights: CL-AI is a storage legumin precursor containing one α-chain and one β-chain. CL-AI in its single stranded state in vivo had inhibitory activity. α- and β-chains are linked by disulfide bond, lossing inhibitory activity in vivo. A cupin domain is involved in α-amylase inhibitory activity. Proteins with a cupin domain inhibit various α-amylases and delay seed germination. Abstract: Proteinaceous α-amylase inhibitors have specialized activities that make some strong inhibition of α-amylases. New α-amylase inhibitors continue to be discovered so far. A proteinaceous α-amylase inhibitor CL-AI was isolated and identified from chickpea seeds. CL-AI, encoded by Q9SMJ4, was a storage legumin precursor containing one α-chain and one β-chain, and each chain possessed a same conserved cupin domain. Amino acid mutation and deficiency of cupin domain would lead to loss of α-amylase inhibitory activity, indicating that it was essential for inhibitory activity. CL-AI(α + β) in its single stranded state in vivo had inhibitory activity. After it was processed into one α-chain and one β-chain, the two chains were connected to each other via disulfide bond, which would cover the cupin domains and lead to the loss of inhibitory activity. The CL-AI(α + β), α-chain and β-chain could inhibit various α-amylases and delay the seed germination of wheat, rice and maize as well as the growth and development of potato beetle larva. Two cupin proteins, Glycinin G1 in soybean and Glutelinin in rice were also found to have inhibitory activity. Our results indicated that the cupin domain is involved in α-amylase inhibitory activity and the proteins with a cupin domain may be a new kind of proteinaceous α-amylase inhibitor.